Analysis of match quality in League of Legends across different times of the day - Peer, Vlastimil; Rejthar, Jan; Krautwurm, Petr; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
This bachelor thesis investigates the influence of time of day on match quality in League of Legends, a popular online game. It explores how players' performance in League of Legends varies across different time periods, considering factors like circadian rhythms and daily activities. By leveraging Riot Games' API, the study analyzes a large dataset and implements LASSO regression, to predict match quality. The results show significant variations in gameplay quality, with early afternoon being optimal for the most competitive games, and late-night to early morning sessions showing decreased quality. This study provides insights for players looking for optimal gaming times and contributes to understanding online gaming behavior in relation to time of day.
Vedoucí práce: Jan Rejthar
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: ekonometrie a operační výzkum [obor bakal. práce]; bakalářské práce; bachelor's theses